Sometimes Less is More: Establishing the Core Symptoms of PTSD. Issue 3 (29th May 2017) - Walton, Jessica L.; Cuccurullo, Lisa‐Ann J.; Raines, Amanda M.; Vidaurri, Desirae N.; Allan, Nicholas P.; Maieritsch, Kelly P.; Franklin, C. Laurel
Abstract : Historically, the symptoms of posttraumatic stress disorder (PTSD) have garnered attention and controversy due to symptom overlap with other disorders. To improve diagnostic specificity, researchers have proposed to reformulate PTSD symptoms into a parsimonious set of core criteria. The core symptoms consisted of recurrent distressing dreams or flashbacks; internal or external avoidance; and hypervigilance or exaggerated startle. The purpose of this study was to examine a previously proposed set of "core" PTSD criteria in identifying cases of PTSD within a veteran sample. Veterans ( N = 383) presenting to a Veterans Affairs (VA) Medical Center PTSD clinic for psychological services were assessed using the Clinician Administered PTSD Scale for DSM‐5 (CAPS‐5). A logistic regression analysis revealed that the core criteria accurately identified 79% of veterans with PTSD ( OR = 11.57). Findings support a parsimonious set of core criteria in the assessment and diagnosis of PTSD. Future studies should replicate these findings in diverse, nonveteran samples.